The Use of Appropriate Technology Based on the ARKAS Application (School Activity Plan and Budget Application) in Primary and Secondary Education Institutions: (Case Study: Blitar City Education Office) - Cahyani, Arik; Marsudi, Kenlies Era Rosalina (International Conference on Digital Business Innovation and Technology Management (ICONBIT), 2024)
The Education Office has one of the main tasks, namely managing and supervising BOS funds in each area under its auspices. The Blitar City Education Office to improve the quality of education at the primary to junior high education level, refers to the Regulation of the Minister of Education and Culture Number 1 of 2018 concerning Technical Instructions for School Operational Assistance. In addition, with the presence of the School Activity Plan and Budget Application (ARKAS), it is hoped that it will be able to realize more efficient educational services to realize advanced and quality human resources. The accounting system with the RKAS application device also has a positive impact on the Blitar City Education Office, such as facilitating the preparation of periodic financial reports (monthly, quarterly, yearly) in accordance with the format that has been set by the Education Office. This activity aims to unite understanding and science related to the administration of BOS funds within the scope of elementary schools in Blitar city. Internship students also help provide directions and answers regarding the use of the Microsoft Excel application which can be said to be a new technology for several groups within the scope of the Blitar City Education Office. Thus, it is hoped that some of the problems that hinder the BOS fund administration flow will be slightly helped to solve.